Financial accounting : volume three - Valix, Conrado T.; Peralta, Jose F. ;Valix, Christian Aris M. (Manila, Philippines : GIC Enterprises & Co. Inc., 2012)
This book is the culmination of the Financial Accounting cluster. It is designed to cover the preparation of statement of financial position, income statement, statement of comprehensive income, statement of changes in equity, statement of cash flows and notes to financial statements.
CHAPTER 1. Financial Statements -- 2. Statement of Financial Position -- 3. Notes to financial statements -- 4. Statement of Comprehensive Income -- 5. Noncurrent Asset held for sale discontinued operation -- 6. Accounting Changes -- 7. Interim Financial reporting -- 8. Operating segment -- 15. SMEs Definition -- 16. SMEs - Qualities and general Features -- 17. SMEs Financial statements -- 18. SMEs Notes to Financial statements -- 19. SMEs Accounting changes -- 20. SMEs Inventories and revenue -- 21. SMEs- Associate and Investment property -- 23. SMEs property, Plant and equipment grant and borrowing cost -- 24. SMEs Intangible Assets -- 25. SMEs Impairment of Assets -- 26. SMEs Provisions and Contingencies.
Keywords: ACCOUNTING